Metaphorical Expressions in Thomas Hardyâ€™s â€œTess of the dâ€™Urbervillesâ€ and their Translation into Albanian - Rapi, Leonard (Mediterranean Journal of Social Sciences, 2012)
Problems posed by the translation of metaphors have often been attributed to linguistic and cultural differences. Those thathave argued that metaphors cannot be translated have pointed to their linguistic and cultural specificity. A different view is that accordingto which metaphors can be translated due to the universality of the perceptual processes underlying metaphorical processes. We foundthat half of all the metaphorical expressions in our corpus of data have been translated by non-metaphorical expressions. While this mayseem as strong support for the argument that metaphors are untranslatable, an analysis of their conceptual structure as well as theirimplications reveals that in some of the metaphorical expressions differences between the ST expressions and the TT translations maynot be accounted for by systemic differences between English and Albanian. Instead, their explanation has to be sought in the influenceof factors other than linguistic or cultural.